The effect of learning and memory on brand equity and it’s implications on financing decisions for pt bsi msme customers in the maqasid syariah perspective - Sarwoto Sarwoto; Asmuni Asmuni; Isnaini Harahap; Rika Surianto Zalukhu (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The study involved 300 MSME customers of PT BSM in North Sumatra, aiming to investigate the impact of learning and memory on financing decisions, with brand equity as a mediating variable. The study also incorporates the Maqasid Shariah perspective. This research adopts a quantitative descriptive approach, employing quota sampling techniques for sample selection and utilizing primary data collected through questionnaires distributed directly to respondents. Respondents' perceptions are measured using Likert scales. The research method utilizes the Structural Equation Modeling (SEM) approach, with a significance level of 5%. Data processing is conducted using Smart PLS 3.0 software, and references are managed through the Mendeley 7th edition program. The findings reveal that customer motivation affects financing decisions in PT BSM's micro-financing. Customer perception does not affect financing decisions in PT BSM's micro-financing. Customer learning does not affect financing decisions in PT BSM's micro-financing. Customer memory does not affect financing decisions in PT BSM's micro-financing. Customer motivation does not affect brand equity. Customer perception affects brand equity. Customer learning affects brand equity. Customer memory affects brand equity. PT BSM's brand equity influences microfinance decisions. Brand equity mediates the influence between customer psychology on microfinance decisions at PT BSM in North Sumatra. The implications of this study encourage PT BSM to enhance awareness of Shariah banking services, emphasizing the importance of Shariah banks in achieving Maqasid Shariah